Identification of Sports Injuries in Young Badminton Men's Athletes 10-11 Years Old - Abdul Aziz Purnomo Shidiq (STKIP Muhammadiyah Kuningan, 2022)
This study aims to determine the cause of injury to male junior athletes 10-11 years old. This Research uses qualitative descriptive methods. Research data sources include male junior athletes 10-11 years old. Data collection techniques use observations, questionnaires, and documentation. The results of this study are minor injuries (cramps, bruises on the legs, and abrasions) and severe injuries (injuries to muscles or tendons/strains, ligaments/sprain). Severe injury (dislocation of the shoulder joint, knee joint, thumb of the hand). So, it can be concluded that mild injury in badminton clubs in Indonesia, including on the criteria, is rare, with a percentage range of 43,3%. Then, minor injuries on the criteria occurred, with a percentage range of 66,67%. Severe injuries in the requirements rarely happen, with a percentage range of 33,33 %. Because injuries to male junior athletes aged 10-11 years are included in the criteria ever occurred due to joking with friends at training, the body is in an unhealthy state, the field is uneven or slippery, not serious when warming up, lack of warm-up, lack of concentration when playing badminton does not cool down after the completion of training, and cooling off not seriously.